مقارنة بين معايرات LH البولي والبروجسترون في تحري الاباضة وبين الايكو المهبلي - ديوب, ميسون (Latakia University Journal -Medical Sciences Series, 2019)
The research was conducted in the Department of Obstetrics and gynecology at the Tishreen university Hospital in the period between 1/1/2018 and 1/1/2019. The study included 90 patients who document ovulation by vaginal ultra sound and LH one-step ovulation, test device (urine) 48 patients unlimited to study of basal body temperature and 70 patients measured progesterone of blood. The results were as follows: 1- The exactitude of progesterone measured in 21 day of menstrual cycle LH one-step ovulation test device (urine) – basal body temperature for document ovulation was 78.05% - 91.94% - 66.67%. Compared with document ovulation by vaginal ultrasound. 2- That in maintain there one not found probative method for document ovulation if we want accurate result we must use more than one method for document ovulation. أجري البحث في قسم التوليد وأمراض النساء بمشفى تشرين الجامعي في الفترة الواقعة بين 1/1/2018 – 1/1/2019 حيث شمل البحث 90 مريضة من مراجعات العيادة النسائية حيث تم تحري الاباضة عند كل المريضات باستخدام الايكو المهبلي وأشرطة LH بالبول، كما تم استخدام مخطط الحرارة الأساسي في تحري الاباضة عند 48 مريضة منهن، وتم عيار البروجسترون في اليوم 21 للدورة عند 70 مريضة منهن حيث تم مقارنة نتائج تحري الاباضة بالطرق السابقة مع نتائج تحري الاباضة باستخدام الايكو المهبلي. وكانت النتائج كالتالي: 1- بلغت دفة استخدام كل من عيار البروجسترون باليوم 21 من الدورة وأشرطة تحري LH بالبول ومخطط الحرارة الأساسي في تحري الاباضة على التوالي 78,05% - 91,94%- 66,67% مقارنة بنتائج الايكو المهبلي 2- بلغت نسبة الدورات الطمثية المنتظمة 80% من الدورات الاباضية في العينة المدروسة مما يؤكد على عدم وجود طريقة مؤكدة بذاتها من الطرق السابقة لحدوث الاباضة وانما لابد من المشاركة بين أكثر من طريقة للوصول الى الدقة المطلوبة.